Efektivitas Kompres Jahe Untuk Menurunkan Nyeri Asam Urat Pada Lansia - Muhammad Sowwam; Sudaryanto; Linda Widyastuti (Universitas Duta Bangsa Surakarta, 2022)
Introduction: Uric acid can cause inflamed pain due to the buildup of purine substances that can form crystals that cause pain. Non-pharmacological treatment efforts, namely by utilizing herbal ingredients known from generation to generation by the community can be efficacious in reducing pain, one of which is ginger. Objectives: To determine the effect ivness of ginger compress on reducing gout pain on eldery Methods: This research is an experimental research (experimental research) with a re-treatment research design which is also called one group pretest posttest. The population of this study were 10 patients. The sampling technique used total sampling. This research instrument uses Easy Touch Urid Acid, ginger compress SOP, NRS. Results: the results of statistical tests using the paired sample t test obtained a p value (Sig 2 tailed) 0.000 < 0.05 , which means that ginger compresses is effective to reducing the intensity of gout painConclusions: Ginger compress is effective in reducing gout pain.